The real options as valuation methodology for a project in the electrical sector (2020)
This paper intends to apply the theory of real options in a construction project for a small hydroelectric power station in Colombia. The calculation of the net present value and the internal rate of return indicate that the project is viable, however, these methodologies are unaware of the option of expansion existing in said project. The article presents the calculation of this option based on the binomial tree methodology, where volatility is obtained through an EGARCH model based on the daily returns of energy prices. It is concluded that the real option makes the project viable, while developing tools that help to work this type of case in the valuations of projects belonging to the energy sector.